2019
DOI: 10.1103/physrevd.99.094002
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic pressure of deconfined QCD matter in presence of strong magnetic field within one-loop approximation

Abstract: Considering the general structure of the two point functions of quarks and gluons, we compute the free energy and pressure of a strongly magnetized hot and dense QCD matter created in heavy-ion collisions. In the presence of a strong magnetic field we found that the deconfined QCD matter exhibits a paramagnetic nature. One gets different pressures in directions parallel and perpendicular to the magnetic field due to the magnetization acquired by the system. We obtain both longitudinal and transverse pressures,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 112 publications
(148 reference statements)
8
62
0
Order By: Relevance
“…Let us explore the covariant structure of the quark selfenergy at finite temperature in an additional presence of magnetic field, which can in general be written [79,80] as…”
Section: Quasiparticle Description Of Hot Qcd Mattermentioning
confidence: 99%
“…Let us explore the covariant structure of the quark selfenergy at finite temperature in an additional presence of magnetic field, which can in general be written [79,80] as…”
Section: Quasiparticle Description Of Hot Qcd Mattermentioning
confidence: 99%
“…The general structures of the quark and gluon self-energy in the presence of the magnetic field have been formulated in Ref. [53] at finite temperature but for zero quark chemical potential. Here we extend it for the case of nonzero quark chemical potential.…”
Section: Strong Magnetic Fieldmentioning
confidence: 99%
“…In the presence of the strong magnetic field, the general structure of quark self-energy can be written from Ref. [53] as…”
Section: Strong Magnetic Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have found the effect of magnetic catalysis [8][9][10], i.e., the enhancement of phase transition temperature of QCD matter in presence of external magnetic field, whereas, some results of inverse magnetic catalysis [11][12][13][14][15][16][17][18] have been reported. Various properties of QCD matter at weak coupling in presence of magnetic field is being studied including the equation of state [19][20][21], transport properties [22][23][24]. Modification of QCD Debye mass and the two point correlation functions of quarks [25] and gluons [26][27][28] i.e., partons have been analyzed recently.…”
Section: Introductionmentioning
confidence: 99%